2001
DOI: 10.1523/jneurosci.21-22-08765.2001
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Anandamide Protects Rat Brain against Acute Neuronal InjuryIn Vivo

Abstract: The endocannabinoid anandamide [N-arachidonoylethanolamine (AEA)] is thought to function as an endogenous protective factor of the brain against acute neuronal damage. However, this has never been tested in an in vivo model of acute brain injury. Here, we show in a longitudinal pharmacological magnetic resonance imaging study that exogenously administered AEA dose-dependently reduced neuronal damage in neonatal rats injected intracerebrally with the Na ϩ /K ϩ -ATPase inhibitor ouabain. At 15 min after injury, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
111
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(120 citation statements)
references
References 67 publications
4
111
0
3
Order By: Relevance
“…For example, 2-AG has been shown to reduce edema formation and enhance functional recovery after brain injury in mice. 46 Similarly, neuroprotective effects for anandamide have been reported in a rat model of ouabaininduced acute brain injury, 21 as well as in neuronal cell cultures, where low doses of anandamide (0.1-0.3 mM) protected cells exposed to hypoxia and glucose deprivation. 47 In contrast, we have recently found that anandamide induces neuronal cell loss after intracerebroventricular (icv) injections in rat brain (I Cernak et al, unpublished observation).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For example, 2-AG has been shown to reduce edema formation and enhance functional recovery after brain injury in mice. 46 Similarly, neuroprotective effects for anandamide have been reported in a rat model of ouabaininduced acute brain injury, 21 as well as in neuronal cell cultures, where low doses of anandamide (0.1-0.3 mM) protected cells exposed to hypoxia and glucose deprivation. 47 In contrast, we have recently found that anandamide induces neuronal cell loss after intracerebroventricular (icv) injections in rat brain (I Cernak et al, unpublished observation).…”
Section: Discussionmentioning
confidence: 82%
“…[15][16][17] Endogenous cannabinoids, such as 2-arachidonoyl-glycerol (2-AG), are generally believed to play a neuroprotective role through actions at CB receptors, and anandamide has also been reported to provide neuroprotection through activation of CB receptors. 4,[18][19][20][21] However, in human neuroblastoma CHP100 and lymphoma U937 cell lines, anandamide induces apoptotic cell death through actions at VR1 receptors, leading to caspase activation. 17 In the present studies, we show that anandamide induces dose-dependent cell death in both rat cortical neuronal and cerebellar granule cells.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabinoids and the CB 1 receptor exert neuroprotective effects in response to neurotoxic stimuli. Arvanil, a synthetic AEA analog, acts against ouabain-induced excitotoxicity via CB 1 receptor activation and prevents neuronal cell death in vivo (29). HU210 displays neuroprotective activity against excitotoxicity in a multiple sclerosis model (30).…”
Section: P Arkinson's Disease (Pd) Is a Common Neurodegenerativementioning
confidence: 99%
“…N-Arachidonylethanolamine (anandamide), a type of NAE in mammalian brain tissue, is an endogenous ligand for the cannabinoid receptor and modulates neurotransmission. Anandamide also can activate vanilloid (capsaicin) receptors and function as an endogenous analgesic (Pertwee, 2001), and appears to be involved in neuroprotection (Hansen et al, 2000;Van der Stelt et al, 2001). In other animal tissues, NAEs have been implicated in immunomodulation (Buckley et al, 2000), synchronization of embryo development (Paria and Dey, 2000), and induction of apoptosis (Sarker et al, 2000).…”
mentioning
confidence: 99%